High-Pressure Torsion: From Miniature Earthquake to the Origin of Life - Edalati, Kaveh; Taniguchi, Ikuo; Floriano, Ricardo; Luchessi, Augusto Ducati [UNESP] (Trans Tech Publications, 2023)
The high-pressure torsion (HPT) method, which is currently used as a severe plastic deformation process to develop advanced structural and functional materials, was first introduced to the public by Bridgman in 1935 as a tool to investigate the mechanism of deep-seated earthquakes. The HPT method was recently introduced as a new platform to simulate astronomical impacts on a miniature scale. Frequent impacts by small solar system bodies (meteoroids, asteroids and comets) about four billion years ago are considered a possible pathway for the delivery or synthesis of essential biomolecules required for life on the Earth. The application of HPT to glycine amino acid led to new justifications for some astronomical phenomena reported in comets or on the Earth such as the formation of alcohol. The extension of this application also led to the introduction of inorganicbiomolecule composites as new functional materials with good biocompatibility.
Keywords: High-Pressure Torsion; Inorganic Compounds; Biomolecules; Severe Plastic Deformation; Ultrafine-Grained Materials